2017
DOI: 10.1039/c7ra09597j
|View full text |Cite
|
Sign up to set email alerts
|

A novel self-assembled supramolecular sensor based on thiophene-functionalized imidazophenazine for dual-channel detection of Ag+ in an aqueous solution

Abstract: A novel dual-channel chemosensor S1 is designed and synthesized, which recognizes Ag+ over other metal ions with high selectivity and sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Upon complexation with Zn 2+ , the FMOs are elevated in energy, effectively reducing the band gap to 2.18 eV, see Figure S40 for the Zn(GD) 2 complex. Hence, the band gap gets reduced upon coordination further supports the metal ion‐driven molecular confinement in the complexes, resulting in fluorescence quenching [20] …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Upon complexation with Zn 2+ , the FMOs are elevated in energy, effectively reducing the band gap to 2.18 eV, see Figure S40 for the Zn(GD) 2 complex. Hence, the band gap gets reduced upon coordination further supports the metal ion‐driven molecular confinement in the complexes, resulting in fluorescence quenching [20] …”
Section: Resultsmentioning
confidence: 90%
“…Hence, the band gap gets reduced upon coordination further supports the metal ion-driven molecular confinement in the complexes, resulting in fluorescence quenching. [20] Among the 30 excited states, Table 1 lists those that significantly contribute to the transition. In the gossyzid monomer, S0!S1, S0!S2, and S0!S3 transitions are apparent, with oscillator strengths: 0.1137, 0.1894, and 0.1032, and excitation energies: 2.74, 2.79, and 2.83 eV, respectively.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The sensor reacted with a color change from yellow to light purple upon introducing Ag + ions in DMSO/Water solution, accompanied by a redshift to 376 nm. Moreover from the fluorescence emission spectra, it was also noticed that the fluorescence intensity of the peak at 547 nm abruptly decreased with the addition of the Ag + to the solution, confirming the selective sensing and detection of Ag + ions over other interfering metal ions [ 70 ] ( Scheme 27 ) . Moreover, the ‘on-off’ mechanism was evaluated by the addition of I − ions to test the reversibility of the sensing mechanism, and was observed that the sensor could be considered an excellent on-off fluorescence sensor, which was evident by the alternating reviving and quenching processes in the fluorescence emission of the sensor 29 -Ag + solution with 2:1 binding stoichiometry.…”
Section: Thiophene Based Chemosensors For Detection Of Cationsmentioning
confidence: 91%
“…The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) of OX(HA) 2 and (OX(HA) 2 -Cu 2 + or (OX(HA) 2 -Fe 3 + complexes were calculated to determine the HOMO-LUMO energy and their energy gap (ΔE). [66,67] The energy gap for the interaction with metal ions was observed to increase 8.64 eV for OX(HA) 2 -Cu 2 + and 5.4 eV for OX(HA) 2 -Fe 3 + complex respectively, with the ΔE value for the receptor being 5.97 eV (Figure 13). It is implied that electron density at LUMO is situated over the carbonyl and azide group of oxalohydrazide, the electron density at HOMO is dispersed over the phenyl ring of OX(HA) 2 .…”
Section: Dft Studiesmentioning
confidence: 98%